RETRACTED: FEATURES OF THE PROJECT-ORIENTED MANAGEMENT OF HIGH-TECHNOLOGY ENTERPRISES - E. D. Dobrova; A. G. Badalova; I. A. Petrova (Модернизация, инновация, развитие, 2017)
Retracted articleThis article is explored the concept of "project portfolio", defined the role and place of project portfolio management in the overall enterprise management structure, the formation of the project portfolio and its limitations. The aim of the article is to study the role and place of project management in the overall enterprise management system, and the relationship of the management processes at diff erent organizational levels.The formation of the strategic projects portfolio of the company – it is an urgent task which is associated with the strengthening of innovation and investment activity of the operating in Russia enterprises. Nowadays, transfer of enterprises activities to an innovative way of development is going on in the face of the deteriorating international situation, Russia's isolation from European countries and the United States, and the implementation of the sanctions policy, changes in the domestic economic and political course. These circumstances, of course, could not aff ect the adjustment of activities and strategic goals of the development of enterprises, at the level of their financial and economic stability. At the same time, the growth of innovation activity in a number of sectors, particularly in high-technology industries, it creates the need for the formation of the project portfolio, which allows to achieve the strategic objectives of enterprises and enhance their competitiveness.During the preparation of the article there were identified a core set of problems faced by the enterprises during the transition to a model of the project management, which is due, primarily, poor project management technologies in Russia, and it is complicated by the lack of a clear definition of objectives and vision benefits for enterprises. In addition, the reasons for the backlog are caused by the low level of project management maturity of the enterprise, which is caused by a lack of personnel with expertise in this field of knowledge.There are identified "bottlenecks" and complexity in the process of project portfolio management at the stage of its formation in this article